AN ANALYSIS OF ANOMALOUS EXCHANGE BETWEEN TEACHER AND STUDENTS IN CLASSROOM INTERACTION - Yati Rachmawati, - (2009)
This study entitled An Analysis of Anomalous Exchange in Classroom Interaction between Teacher and Students aims to seek what are the typical anomalous exchange that appear in classroom interaction naturally, to explore in what occasion the anomalous exchange normally occur, and to seek what the effect of classroom interaction to the occurrence of anomalous exchange. The subjects of the study were two English teachers and about 120 students of an English classroom from four different classes and grades. The data were collected through video recordings of five English lessons, classroom observations, and interviewing the teacher. The data collected were analyzed by applying Suherdi's (2006) model focusing on anomalous exchange analysis. Generally, the findings show the occurrence of each type of anomalous exchange affected by the situation of the classroom. The situation covers the learning activity, grade of the class and the characteristic of the class. In addition, type of classroom interaction and type of teacher's question also affected the occurrence of anomalous exchange. The data reveals that elliptical exchange frequently occurs in the classroom where the learning activity was listening practice. Three of four observed class had listening practice as the learning activity when the research was done. There are 27 exchanges or about 20.9% of elliptical exchange in lesson 3. While in lesson 4 there are 13 exchanges or it is about 23.2% and there are 14 exchanges in lesson 1 or it is about 13.2%. Meanwhile, the defective exchange occurrence dominantly occurs in lesson 2 where the learning activity was grammar explanation and the interaction was dominated by teacher talk. Beside the occurrence of defective exchange is also affected by the characteristic of the class, which tends to be passive. There are 13 exchanges of defective exchange found in lesson 2. Above all, this research has proved that certain type of anomalous exchange occurrence depends on the classroom activity applied by the teacher such as listening practice, reading, writing or speaking class. It also depends on the types of question that teacher asks.